Dynamics of Islamic Economic Development in the Past a Decade: A Bibliometric Analysis and Systematic Literature Review - Indah Syafa'atul Ula; Abdul Rohman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the dynamics of Islamic economic and financial development over the past decade (2014–2024) through a bibliometric approach and systematic literature review (SLR). Data were collected from 600 Scopus-indexed scientific articles using the PRISMA protocol and analyzed with the help of the Biblioshiny-R software. The results of the study reveal a significant upward trend in publications, with an annual growth rate of 16.36%, predominantly contributed by Malaysia, Indonesia, and the United Kingdom. The most prominent research topics include Islamic banking, Sharia governance, Islamic fintech, sukuk, and sustainability. International collaboration is notably high, with 33% of the publications resulting from cross-country cooperation. The study identifies several gaps in the literature, such as the limited use of empirical approaches, the low integration of maqashid sharia principles with the Sustainable Development Goals (SDGs), and the lack of cross-country and multidisciplinary research. These findings suggest that future research should focus on more contextual, interdisciplinary, and globally responsive exploration. Thus, this study not only maps the comprehensive development of Islamic economic literature but also provides a strategic foundation for formulating a more relevant and sustainable research agenda.